A comparative macro-anatomic, mechanical and geometric morphometries study on tree and ground squirrel and rat - Hakan Yalçın; Seyit Ali Kayış; Atilla Arslan (Eurasian Journal of Veterinary Sciences)
This study is carried out comparatively on throe rodent species. There were ten matured three squirrels (5 male and 5 female), ten matured ground squirrels (4 male and 6 female), and ten 60 day old rats (5 male and 5 female). Study material was lateral side of right mandible. Mandibles of tree and ground squirrels and rats were compared m aero-anatomically. Comparing to squirrels, rats had a bone tip on the lateral side of rostro-ventral of mandibular notch, coronoid process was short and plain, and in the medial side, pterygoid fossa was deepper in the ground squirrels but not in the rats. Unlike mammals, three species had masseteric ridge that frames masseteric fossa dorsally and ventrally. In terms of some metric measurements (Sd, Sv, Ad, Td) taken on mandible, ground squirrel and rat were very similar. In addition, mechanical advantageous of masticatory muscles on the mandible of three species were calculated. In general, comparing to ground squirrel, tree squirrel had more mechanical advantageous of jaw muscles. However, comparison ot three squirrel to rat showed that tree squirrel had more advantageous in two jaw muscles (Sd, Sv), had disadvantageous in one masticatory muscles (Ad), and had no differences for the other two jaw muscles (Tv, Td). Comparing rats to ground squirrels, in terms of jaw muscles, showed that rats had more advantageous in three jaw muscles (Sd, Ad, Tv), but had no differences lor the other two (Sv, Td). In terms of dorsal fibers of the temporal muscles (Td), there were no differences for three species. In this study, three rodent species were compared for species and se* factors via Geometric Morphometries methods. For this purpose, 16 homologous landmarks, on the mandible, were used. It is found that the first two principle components (PCI and PC2) were able to separate three species clearly. The first two principle components were able to reveal 71% of the total shape variation (PCI: 37%, PC2: 34%). In addition, movements of landmarks in different species were analysed by means of deformation grid. Orthogonal comparison of shape data showed that three species differs statistically significantly.